RELEVANSI BERMAZHAB (Reorientasi dari Bermazhab Qaulì menuju Bermazhab Manhajì) - Imam Mustofa (Universitas Islam Negeri Mataram, 2013)
This article discusses the relevance of following a certain Islamic legal school (mazhab) in this era, where science advances sophisticatedly and media grows rapidly. Educational institutions have also emerged every where. Islamic sciences or Islamic studies have been taught at various educational institutions. As time has passed, situations and conditions, social setting and socio-cultural conditions have also changed. This era is different from the social settings and the conditions at the time of the first scholars or jurists conducted ijtihad. Do well-trained Muslims in fiqh and and usul al-fiqh still need to follow a certain madzhab or even to blindly follow it (taqlid)? If so, to what extent are they allowed to follow a madzhab, at the level of methodological aspects or at the level of doctrinal ones? This article responses these questions. This is a library research that uses usul fiqh approach. Data are collected from the work usul fiqh and fiqh, both classic and contemporary work. This article argues that for those who are qualified to do ijtihad is not allowed to follow the product of a madzhab’s legal doctrines. However, for those who have no competence to do ijtihad are encouraged to follow Islamic legal doctrines from a particular Islamic school that they think most relevant to their own contexts.